TBC1D14 regulates autophagosome formation via Rab11- and ULK1-positive recycling endosomes. - Longatti, A; Lamb, C; Razi, M; Yoshimura, S; Barr, F; Tooze, SA (2012)
Autophagy is a bulk degradation process characterized by the formation of double membrane vesicles called autophagosomes. The exact molecular mechanism of autophagosome formation and the origin of the autophagosomal membrane remain unclear. We screened 38 human Tre-2/Bub2/Cdc16 domain-containing Rab guanosine triphosphatase-activating proteins (GAPs) and identified 11 negative regulators of starvation-induced autophagy. One of these putative RabGAPs, TBC1D14, colocalizes and interacts with the autophagy kinase ULK1. Overexpressed TBC1D14 tubulates ULK1-positive recycling endosomes (REs), impairing their function and inhibiting autophagosome formation. TBC1D14 binds activated Rab11 but is not a GAP for Rab11, and loss of Rab11 prevents TBC1D14-induced tubulation of REs. Furthermore, Rab11 is required for autophagosome formation. ULK1 and Atg9 are found on Rab11- and transferrin (Tfn) receptor (TfnR)-positive recycling endosomes. Amino acid starvation causes TBC1D14 to relocalize from REs to the Golgi complex, whereas TfnR and Tfn localize to forming autophagosomes, which are ULK1 and LC3 positive. Thus, TBC1D14- and Rab11-dependent vesicular transport from REs contributes to and regulates starvation-induced autophagy.